Empirically Investigating the Presence of Positive Accounting Research as the Meta- Theory for Accounting Academics: : Further Evidence from Saudi Arabia - Al-Adeem, Khalid (The Journal of Accounting and Management, 2021)
This study empirically explores the extent to which accounting academics in Saudi Arabia apply agency theory conceptually and methodologically. All accounting academics in Saudi Arabia have been awarded decorates abroad from various institutions worldwide, which makes them suitable subjects to investigate whether they are dominated by positive accounting methodology to assess its global impact. Fifty respondents volunteered to take the web-based questionnaire. Almost reaching an agreement that agency theory was originated in accounting conventions, sampled accounting academics concur that such a theory is an accounting theory. Controversially, while they agree with propositions of Jensen and Meckling, (1976), they are unsure that agency theory is the most suitable theory for accounting research and are undecided in deeming the view that C.E.O.s as agents and shareholders as principals is the only correct way to build understanding on the nature of the corporation. They are generally aware of positive accounting methodology and are exposed to it in their doctoral studies. Not constraining accounting inquiry to phenomena that behave rationally, they nonetheless assume rationality in almost all observed behavior in accounting.